Selected research issues in the Malaysian agricultural sector - Jamal Othman,; Yaghoob Jafari, (Penerbit Universiti Kebangsaan Malaysia, 2014)
The agriculture sector remains a signfficant developmenfta sector in Malaysia even though its share to the nation GDp has shrunk pronouncedly from some 30% in the 1970s to only 7% in 20 I 3. Such statistics moy not, however, reflect the true significance of the Malaysian agricultural economy. Ihhile the agricultural sector of the past decades was mainly associated with the production of raw commodities and primary processing activities, its curyent importance maybe seen in terms of the sector b contribution to the total economy, via its inter-sectoral linkages and multi-functional roles. This paper highlights a number of issues that have bearings on thefuture roles of the agricultural economy in Malaysia. These include the emerging notion of agricultural multi-functtonality, fficient allocation of land to various agricultural sub-sectors, deforestation and oil palm expansion, shortages ofdomestic laboafood-fuel dilemma, and extensive use ofagrochemicals. Policy implications and/or suggestionsforfuture research are deliberatedfor each issue